Facial Expression Overrides Lumbopelvic Kinematics for Clinical Judgements about Low Back Pain Intensity - A. Courbalay; T. Deroche; M. Descarreaux; E. Prigent; J. O'Shaughnessy; M.-A. Amorim (Pain Research and Management)
Background. Through real-time behavioral observation systems, pain behaviors are commonly used by clinicians to estimate pain intensity in patients with low back pain. However, little is known about how clinicians rely on pain-related behaviors to make their judgment. According to the Information Integration Theory (IIT) framework, this study aimed at investigating how clinicians value and integrate information from lumbopelvic kinematics (LK), a protective pain behavior, and facial expression intensity (FEI), a communicative pain behavior, to estimate pain in patients with chronic low back pain (cLBP). Methods. Twenty-one experienced clinicians and twenty-one novice clinicians were asked to estimate back pain intensity from a virtual character performing a trunk flexion-extension task. Results. Results revealed that both populations relied on facial expression and that only half of the participants in each group integrated FEI and LK to estimate cLBP intensity. Among participants who integrated the two pain behaviors, averaging rule predominated among others. Results showed that experienced clinicians relied equally on FEI and LK to estimate pain, whereas novice clinicians mostly relied on FEI. Discussion. The use of additive rule of integration does not appear to be systematic when assessing others’ pain. When assessing pain intensity, communicative and protective pain behaviors may have different relevance.